Oxidative damage to plants : antioxidant networks and signaling - Ahmad, Parvaiz (San Diego, CA : Academic Press, 2014)
With contributions that review research on this topic throughout the world, this book covers key areas of discovery, from the generation of reactive oxygen species (ROSs), their mechanisms, quenching of these ROSs through enzymatic and non-enzymatic antioxidants, and detailed aspects of such antioxidants as SOD, CAT and ascorbate.--
Includes bibliographic references and index.
Keywords: Plants -- Effect of oxygen on; Oxidative stress; Active oxygen; Antioxidants